Indifferent or Enthusiastic? Virtual Audiences Animation and Perception in Virtual Reality - Glémarec, Yann; Lugrin, Jean-Luc; Bosser, Anne-Gwenn; Collins Jackson, Aryana; Buche, Cédric; Latoschik, Marc Erich (Frontiers in Virtual Reality, 2021)
In this paper, we present the design and evaluations of a virtual audience simulation system for Virtual Reality (VR). The system is implementing an audience attitude perception model controlling the nonverbal behaviors of virtual spectators, such as facial expressions or postures. Groups of virtual spectators are controlled by a set of nonverbal behavior rules. Each rule specifies a nonverbal behavior category: posture, head movement, facial expression and gaze direction as well as three parameters: type, frequency and proportion. In a first user-study, we asked participants to create sets of non-verbal behaviour parameters to simulate different attitudes. Participants were immersed in VR and manipulated the non-verbal behaviours of single virtual spectator to match a specific levels of engagement and opinion toward the presenter. In a second user-study, we used these parameters to design different types of virtual audiences with our nonverbal behavior rules and evaluated their perceptions. Our results demonstrate our system’s ability to create virtual audiences with three types of different perceived attitudes: indifferent, critical, enthusiastic. The analysis of the results also lead to a set of recommendations and guidelines regarding attitudes and expressions for future design of audiences for VR therapy and training applications.